Designing a STEM-PjBL E-Module to Foster Mathematical Representation Ability and Habits of Mind: Evidence from a Secondary School Field Trial - Muhammad Faiz Fadillah; Yumiati Yumiati; Sudirman Sudirman; Ronaldo Rafael Olivero-Acuña (Indonesian Educational Research Journal, 2026)
A critical gap persists in Indonesian mathematics education: no e-module currently in use simultaneously targets both mathematical representation ability and Habits of Mind (HoM) through a physics-engineering context. This study aimed to develop and validate a STEM-PjBL mathematics e-module for Grade XI students built around a through-truss bridge design challenge. Using Thiagarajan’s 4D model, the module was developed and reviewed by three domain experts (content, media, language), then piloted in 2026 with 25 Grade XI students in Jakarta using a one-group pretest-posttest design. Data were collected through expert validation sheets, a mathematical representation test (α = 0.8604), a practicality questionnaire (α = 0.9637), and a post-intervention HoM questionnaire (α = 0.9286); all student instrument items were statistically valid. Expert validation yielded a composite score of 84.47% (content: 73.91%; media: 92.60%; language: 86.90%). Field trial results showed statistically significant improvement in representation ability (t = 22.305, p < 0.0001; N-Gain = 0.35, classified as moderate gain by Hake’s criterion), with 56% of students reaching the individual mastery threshold (KKTP ≥ 65). Post-intervention HoM averaged 69.32% and practicality 70.23%. Correlation analyses revealed meaningful associations among all three outcomes: HoM–representation (r = 0.682), practicality–representation (r = 0.740), and HoM–practicality (r = 0.898). The module is statistically effective and validly designed, though adaptive scaffolding is needed for students with low entry-level competence. Limitations include the absence of a control group, a single-site sample, and the post-only HoM measurement design.